A theorem on diophantine approximations - Vilius Stakėnas (Lietuvos Matematikos Rinkinys)
A result is proved on approximation of irrational numbers by rational ones, satisfying some requirements on their multiplicative structure. The statement is comparable with that one on diophantine approximations with square-free integers.